Exploring the Impact of Self-Esteem on Online Self-Disclosure of Second Account Users on Instagram: Trust as a Mediator - Lase, Christianty Charisda; Kristinawati, Wahyuni; Murti, Heru Astikasari Setya (Kuras Institute, 2024)
This study aims to determine whether trust plays a role in mediating the influence of self-esteem on online self-disclosure of second Instagram account users. The research method used is a quantitative method carried out using multiple linear regression using the Process Hayes model 4 program with the bootstrapping method to test the mediation effect. RSES (Rosenberg's Self-esteem Scale) modified by Tombeng and Yuwono is used to measure self-esteem; Rotenberg's interpersonal trust scale which has been modified by researchers is used to measure trust; and the Revised Self-Disclosure Scale (RSDS) which has been modified by researchers is used to measure online self-disclosure. Participants totaled 251 students from the UKSW Faculty of Psychology. The results showed that trust mediates the influence of self-esteem on online self-disclosure (ab = .167, SE = .057, 95%, CI [.071, .296]). Self-esteem was found to increase the emergence of a sense of trust which then led to online self-disclosure.